PERFORMA POMPA SEKUNDER PADA SISTEM PENDINGIN REAKTOR NUKLIR - Anugrah, Dwi Permana; Nuramal, Agus; Puspawan, Angky; Falah, Sabilul (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2024)
Secondary pump in the reactor nuclear works move fluid in the reactor with take hot from system primary coolant and discard it to environment. For support safety reactor nuclear this need done study to performance pumps secondary being one​​ system cooler reactor. Methodology study consists from studies literature, observation field, and data collection. Pump used as pump secondary to the system cooler Reactor nuclear This is centrifugal water pump with rate Genre volumetric 4500 liters/ minute with capacity adjustable water flow with characteristics heat exchanger. From the results calculation of data taken on three different day​show mark increased efficiency due to rising mark WP. This matter proves that mark WP on pump system cooler secondary reactor nuclear influence mark efficiency from pump secondary used.​ For mark efficiency highest there at 11:00 with​mark amounting to 18.288%.